Rediscovering hope in a new era: Possibilities for the radical tradition of adult education - Michael Law (Adult Education Research Conference, 1996)
In the context of globalization, socialism’s crisis of theory and practice on the one hand and the consequences of unbridled capitalism and new-liberal ideologies and practice on the other have brought the radical tradition of adult education back to its roots.